Utopía y política en el pensamiento científico latinoamericano de la segunda mitad del siglo XX: La contribución de Oscar Varsavsky. - Castro Martinez, Christian J. (Latin American Research Review, 2022)
This article explores the Argentine chemist Oscar Varsavsky’s concept of attainable utopias. Although most interpretations of Varsavsky’s work concentrate on his important contributions to science and technology studies in Latin America, I argue that his idea of scientific style belongs to a much larger theoretical framework. I explore how the author adapted new scientific disciplines to the liberatory project of attainable utopias. First, I introduce Varsavsky’s political and intellectual development. Second, I discuss his ideas of attainable utopias and utopic engineering, and the articulation of these with the notions of social change and power. Finally, I present the concepts of pueblo-centric rationality and social styles.